Potato Disease Prevalence and Quality Performance Under Four Soil Health-Related Practices - Kate Binzen Fuller; Kusum Adhikari; Alexander Maas; Christopher McIntosh; Carl Rosen; James E. Crants; Robert P. Larkin; Kim Zitnick Anderson; Anna Stasko; Julie Pasche; Kenneth Frost; Jeff Miller; et al. (American Journal of Potato Research, 2026)

Energy balance related lifestyle factors and risk of endometrial and colorectal cancer among individuals with lynch syndrome: a systematic review - Adriana M. Coletta; Susan K. Peterson; Leticia A. Gatus; Kate J. Krause; Susan M. Schembre; Susan C. Gilchrist; Mala Pande; Eduardo Vilar; Y. Nancy You; Miguel A. Rodriguez-Bigas; Larkin L. Strong; Patrick M. Lynch; et al. (Familial Cancer, 2019)

The European Marine Observation and Data Network (EMODnet): Visions and Roles of the Gateway to Marine Data in Europe - Belén Martín Míguez; Antonio Novellino; Matteo Vinci; Simon Claus; Jan-Bart Calewaert; Henry Vallius; Thierry Schmitt; Alessandro Pititto; Alessandra Giorgetti; Natalie Askew; Sissy Iona; Dick Schaap; et al. (Frontiers in Marine Science, 2019)

The Role of Stakeholders in Creating Societal Value From Coastal and Ocean Observations - Bev Mackenzie; Louis Celliers; Luiz Paulo de Freitas Assad; Johanna J. Heymans; Nicholas Rome; Julie Thomas; Clarissa Anderson; James Behrens; Mark Calverley; Kruti Desai; Paul M. DiGiacomo; Samy Djavidnia; et al. (Frontiers in Marine Science, 2019)

Oxygen as a control on sea floor biological communities and their roles in sedimentary carbon cycling - Clare Woulds; Greg L. Cowie; Lisa A. Levin; Johan H. Andersson; Jack J. Middelburg; Sandra Vandewiele; Peter A. Lamont; Kate E. Larkin; Andrew J. Gooday; Stefanie Schumacher; Christine Whitcraft; Rachel M. Jeffreys; et al. (Limnology and Oceanography, 2007)
13 C tracer experiments were conducted at sites spanning the steep oxygen, organic matter, and biological community gradients across the Arabian Sea oxygen minimum zone, in order to quantify the role that benthic fauna play in the short‐term processing of organic matter (OM) and to determine how this varies among different environments. Metazoan macrofauna and macrofauna‐sized foraminiferans took up as much as 56 ± 13 mg of added C m −2 (685 mg C m −2 added) over 2–5 d, and at some sites this uptake was similar in magnitude to bacterial uptake and/or total respiration. Bottom‐water dissolved oxygen concentrations exerted a strong control over metazoan macrofaunal OM processing. At oxygen concentrations −1 (0.16 ml L −1 ), metazoan macrofauna were able to take advantage of abundant OM and to dominate OM uptake, while OM processing at O 2 concentrations of 5.0 µmol L −1 (0.11 ml L −1 ) was dominated instead by (macrofaunal) foraminiferans. This led us to propose the hypothesis that oxygen controls the relative dominance of metazoan macrofauna and foraminifera in a threshold manner, with the threshold lying between 5 and 7 µmol L −1 (0.11 to 0.16 ml L −1 ). Large metazoan macrofaunal biomass and high natural concentrations of OM were also associated with rapid processing of fresh OM by the benthic community. Where they were present, the polychaete Linopherus sp. and the calcareous foraminiferan Uvigerina ex gr. semiornata , dominated the uptake of OM above and below, respectively, the proposed threshold concentrations of bottom‐water oxygen.